Automated radiosynthesis of [(68)Ga]Ga‐PSMA‐11 and [(177)Lu]Lu‐PSMA‐617 on the iPHASE MultiSyn module for clinical applications - Wichmann, Christian W. (J Labelled Comp Radiopharm, 2020)
Prostate‐specific membrane antigen (PSMA)‐targeted imaging and therapy of prostate cancer using theranostic pairs is rapidly changing clinical practice. To facilitate clinical trials, fully automated procedures for the radiosyntheses of [(68)Ga]Ga‐PSMA‐11 and [(177)Lu]Lu‐PSMA‐617 were developed from commercially available precursors using the cassette based iPHASE MultiSyn module. Formulated and sterile radiopharmaceuticals were obtained in 76 ± 3% (n = 20) and 91 ± 4% (n = 15) radiochemical yields after 17 and 20 min, respectively. Radiochemical purity was always >95% and molar activities exceeded 792 ± 100 and 88 ± 6 GBq/μmol, respectively. Quality control showed conformity with all relevant release criteria and radiopharmaceuticals were used in the clinic.